The backward end-cap for the PANDA electromagnetic calorimeter. (13th February 2015) - Capozza, L; Maas, F E; Noll, O; Pineiro, D Rodriguez; Valente, R
Abstract: The PANDA experiment at the new FAIR facility will cover a broad experimental programme in hadron structure and spectroscopy. As a multipurpose detector, the PANDA spectrometer needs to ensure almost 4π coverage of the scattering solid angle, full and accurate multiple-particle event reconstruction and very good particle identification capabilities. The electromagnetic calorimeter (EMC) will be a key item for many of these aspects. Particle energies ranging from some MeVs to several GeVs have to be measured with a relative resolution of 1% ⊕ 2%/√ E /GeV . It will be a homogeneous calorimeter made of PbWO4 crystals and will be operated at -25°C, in order to improve the scintillation light yield. With the exception of the very forward section, the light will be detected by large area avalanche photodiodes (APDs). The current pulses from the APDs will be integrated, amplified and shaped by ASIC chips which were developed for this purpose. The whole calorimeter has been designed in three sections: a forward end-cap, a central barrel and a backward end-cap (BWEC). In this contribution, a status report on the development of the BWEC is presented.